Identifying hub genes of calcific aortic valve disease and revealing the immune infiltration landscape based on multiple WGCNA and single-cell sequence analysis - Wang, Kan; Zheng, Qiang; Liu, Xing; Geng, BingChuan; Dong, NianGuo; Shi, JiaWei (Frontiers in Immunology, 2022)
Abstract Background: Calcific aortic valve disease (CAVD) is a progressive fibrocalcific disease that can only be treated with valve replacement. This study was aimed to determine the role of hub genes and immune cell infiltration in the progression of CAVD. Methods: In this study, bioinformatic analysis was used to identify the hub genes involved in Calcific aortic valve diseases (CAVD). The datasets were downloaded from the Gene Expression Omnibus (GEO) database and the Array Express database. Gene expression differences were evaluated using both pathway and gene ontology (GO) analysis. Weighted gene co-expression network analysis (WGCNA) and differentially expressed gene (DEG) were used to screen hub genes. The CIBERSORT algorithm was used to analyze the immune infiltration into the calcified aortic valve between the hub genes high expression and low expression groups. We also have performed the single-cell RNA sequencing (scRNA-seq) data in our center, which has collected 6 different human aortic valve leaflets. The expressions of hub genes were identified in human and mice samples by quantitative real-time polymerase chain reaction (qPCR), immunohistochemical, immunofluorescence, and ELISA assay, and clinical features of the patients were investigated. Results: A total of 454 differential genes were obtained in combined GEO database. Then, WGCNA was used to find twelve co-expression modules in Array Express database, of which, one hub module (brown module) was most correlated with CAVD. A total of 2 hub genes were acquired by combining differential genes: S100A8, and S100A9. Compared with the hub gene low expression group, the high expression group contained a higher proportion of activated NK cells (p <0.01) and macrophages M1 (p <0.05). Furthermore, these results were also verified in mice and human samples by immunofluorescence, immunohistochemical, qPCR and Elisa analysis. Finally, the location of S100A8 and S100A9 were confirmed in monocyte and macrophage by immunofluorescence in human aortic valve. Conclusion: The present results demonstrated that S100A8 and S100A9 were two hub genes of CAVD, which may play an important role in the development of CAVD through immune-related signal pathways .